Phase 3 Trial of Selpercatinib in Advanced RET-Mutant Medullary Thyroid Cancer - Hadoux, Julien; Elisei, Rossella; Brose, Marcia S; Hoff, Ana O; Robinson, Bruce G; Gao, Ming; Jarzab, Barbara; Isaev, Pavel; Kopeckova, Katerina; Wadsley, Jonathan; Führer, Dagmar; Keam, Bhumsuk; et al. (The New England journal of medicine, 2023)
BACKGROUND: Selpercatinib, a highly selective, potent RET inhibitor, has shown efficacy in advanced RET-mutant medullary thyroid cancer in a phase 1-2 trial, but its efficacy as compared with approved multikinase inhibitors is unclear. METHODS: We conducted a phase 3, randomized trial comparing selpercatinib as first-line therapy with the physician's choice of cabozantinib or vandetanib (control group). Eligible patients had progressive disease documented within 14 months before enrollment. The primary end point in the protocol-specified interim efficacy analysis was progression-free survival, assessed by blinded independent central review. Crossover to selpercatinib was permitted among patients in the control group after disease progression. Treatment failure-free survival, assessed by blinded independent central review, was a secondary, alpha-controlled end point that was to be tested only if progression-free survival was significant. Among the other secondary end points were overall response and safety. RESULTS: A total of 291 patients underwent randomization. At a median follow-up of 12 months, median progression-free survival as assessed by blinded independent central review was not reached in the selpercatinib group and was 16.8 months (95% confidence interval [CI], 12.2 to 25.1) in the control group (hazard ratio for disease progression or death, 0.28; 95% CI, 0.16 to 0.48; P<0.001). Progression-free survival at 12 months was 86.8% (95% CI, 79.8 to 91.6) in the selpercatinib group and 65.7% (95% CI, 51.9 to 76.4) in the control group. Median treatment failure-free survival as assessed by blinded independent central review was not reached in the selpercatinib group and was 13.9 months in the control group (hazard ratio for disease progression, discontinuation due to treatment-related adverse events, or death, 0.25; 95% CI, 0.15 to 0.42; P<0.001). Treatment failure-free survival at 12 months was 86.2% (95% CI, 79.1 to 91.0) in the selpercatinib group and 62.1% (95% CI, 48.9 to 72.8) in the control group. The overall response was 69.4% (95% CI, 62.4 to 75.8) in the selpercatinib group and 38.8% (95% CI, 29.1 to 49.2) in the control group. Adverse events led to a dose reduction in 38.9% of the patients in the selpercatinib group, as compared with 77.3% in the control group, and to treatment discontinuation in 4.7% and 26.8%, respectively. CONCLUSIONS: Selpercatinib treatment resulted in superior progression-free survival and treatment failure-free survival as compared with cabozantinib or vandetanib in patients with RET-mutant medullary thyroid cancer. (Funded by Loxo Oncology, a subsidiary of Eli Lilly; LIBRETTO-531 ClinicalTrials.gov number, NCT04211337.).
Keywords: nádory štítné žlázy; Proto-Oncogene Proteins c-ret; Carcinoma, Neuroendocrine; protoonkogenní proteiny c-ret; pyridiny; Quinazolines; lidé; Thyroid Neoplasms; neuroendokrinní karcinom; Antineoplastic Agents; protinádorové látky; progrese nemoci; Disease Progression; piperidiny; Pyridines; chinazoliny; Piperidines; Humans